Cultural Competence and Cultural Sensitivity Education in University Nursing Courses. A Scoping Review - Gradellini, Cinzia; Gómez-Cantarino, Sagrario; Dominguez-Isabel, Patricia; Molina-Gallego, Brigida; Mecugni, Daniela; Ugarte-Gurrutxaga, María Idoia (Frontiers in Psychology, 2021)
Abstract When assessing the fragility that characterizes the health of an immigrant person, a culturally competent transformation of the nurse-patient teaching-learning process is necessary. Therefore, it is considered essential to incorporate cultural competence and intercultural communication in higher nursing education. Objective: To determine the content and knowledge of cultural competence and intercultural communication offered in higher education in nursing courses. Design: The Campinha-Bacote model of cultural competence was used as the primary reference. Method: A scoping review was conducted about studies published in the period 2003 and 2020. The research was conducted between May and October 2020. More than a hundred documents (books, chapters, articles, conference proceedings) have been consulted. Results: Undergraduate nursing courses and postgraduate education move towards promoting cultural competence and sensitivity through teaching strategies. Conclusions: Teaching projects that combine multiple competencies are more effective, including teacher training. A predominant element is a need for continuous and transversal projects. University nursing education must adapt culturally competent curricula.